Anisotropy of wear and tribocorrosion properties of L-PBF Ti6Al4V - Heng Liu; Xin Huang; Shiyu Huang; Lijie Qiao; Yu Yan (Journal of Materials Research and Technology, 2023)
Additive manufactured Ti6Al4V has shown high tensile anisotropy. The tribocorrosion properties involve the coupling of mechanical wear and surface corrosion, and its anisotropy is unclear. In this study, the corrosion resistance of the horizontal (XOY) plane and the vertical (V) plane was compared by electrochemical tests. The wear resistance and tribocorrosion resistance of different planes of laser powder bed fusion (L-PBF) Ti6Al4V were tested by using zirconia ball as friction pair. The results show that the corrosion resistance of the V plane was better than that of the XOY plane. However, the wear and tribocorrosion resistance recorded for the XOY plane was better than that of the V plane. The columnar crystals along the building direction led to the anisotropy of wear and tribocorrosion of L-PBF Ti6Al4V.